PERAN LAYANAN INFORMASI MEDIA FILM SEBAGAI TINDAKAN PREVENTIF TERHADAP SEKS BEBAS PADA SISWA KELAS IX SMP N 8 SURAKARTA TAHUN PELAJARAN 2021/2022 - Handriyan, Deva (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2023)
Abstract: This study aims to find out about the Role of Film Media Information Services as a Preventive Measure against Free Sex Behavior in grade IX students carried out at SMP N 8 Surakarta. This research is a qualitative descriptive research. The subjects in this study were class IX students totaling 3 students, parents of all three students and teachers of guidance and counseling. The data obtained in this study used observation techniques, interviews and documentation. The observation technique is carried out by researchers by observing the behavior of the subject as well as the environment then continued with interview techniques for the subject, parents of the subject as well as guidance and counseling teachers to obtain more accurate data and strengthened by documentation techniques. The validity of the data used is the triangulation of sources and time. Qualitative data analysis based on a systematic process, namely by reducing data, presenting data and drawing conclusions. Based on data analysis, it was concluded that grade IX students of SMP N 8 Surakarta for the 2022/2023 Academic Year there were several students who were indicated to have free sex behavior and were still lacking about preventing free sex behavior due to lack of information they had. After being provided with information services with film media, students can better understand it. The conclusions of this study show that students' activeness in responding and asking questions when providing services, increased understanding after the subject received information and the cooperation between several schools and families in helping to prevent free sex behavior. Keywords: The Role of Film Media Information Services, Preventive, Promiscuous Sex Behavior